Comment référer à une classe ? Variations autour du concept de PARCOURS - Lucie Gournay (Corela)
The concept of scanning is a good start to illustrate metalinguistic problems inside the Théorie des Opérations Prédicatives et Enonciatives. It’s also a useful concept when talking about the process of class reference. In fact, if there are various definitions of scanning more or less divergent, it’s usually taken for granted that this particular enunciative operation allows the construction of a class or a set of potential values. For instance, in “any questions?” the speaker refers to a class of occurrences, and “in any question?” the speaker refers to set of possible values for one occurrence. I argue against this consensual view, showing that scanning is just only one enunciative operation among others that allow class reference. Of course, my claim will require that I explain what the proper definition of scanning should be. In this study, I discuss a large sample of markers traditionally called scanning operators: any, or, either, which, each, every... in order to sort them out and explain some of their compatibilities or incompatibilities when class reference is at stake.